Improved subsurface drainage increased small grain cereal yield but not the soil carbon stock of a boreal clay soil - Lång, Kristiina; Honkanen, Henri; Kaseva, Janne; Lemola, Riitta; Uusitalo, Risto (Scientific Agricultural Society of Finland, 2026)
Removal of excess water by soil drainage is a prerequisite of proper yields in boreal agriculture. A functioning drainage system enables farming operations, maintains yields and improves the environmental performance of a field plot. As carbon input to soils in crop residues increases with the yield, increased crop production might benefit the carbon balance of the soil. We document the effects of drainage renovation on the yield and crop residue production of spring cereals at a long-term experimental site on Protovertic luvisol in south-western Finland and discuss their relevance for soil carbon sequestration. The yield and amount of crop residues were monitored continuously before (1985–1990) and after (1992–1997) a drainage renovation. The cereal yields almost doubled, reaching the current average yields, and the amount of crop residue increased by 30% after the improvement of the drainage system. This was, however, not significantly reflected in the soil carbon stock. Drainage renovation can be considered sustainable intensification that provides long-term benefits for crop production, but carbon sequestration likely requires more carbon input than is available in the cereal straw.
Keywords: drainage renovation; crop yield; straw yield; carbon sequestration